Pedagogia do esporte: livro didático aplicado aos jogos esportivos coletivos - Galatti, Larissa Rafaela; Paes, Roberto Rodrigues; Darido, Suraya Cristina [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2010)
The study deals with the pedagogical possibilities of text books as a resource for Physical Education (PE) classes based on sports, specifically team sports. It started from a bibliographical review on the cited terms and after that we advanced our studies in order to propose a didactic text book on Team Sports for PE classes considering two benchmarks: one technical-tactic and the other social-educational. In order to do so, we used methods from linguistics, and the development of a Didactic Sequence allowed the selection and distribution of the contents to be presented in the book in an orderly and judicious way. The focus in Team Sports is justified by its social-cultural insertion and by the need to transform recent studies into new pedagogical procedures for practicing them. The didactic text book, as well as the adequate preparation of the professionals who will use it, is pointed out as facilitator in the process of teaching, experiencing and learning team sports.

O estudo trata das possibilidades pedagógicas do livro didático (LD) como recurso nas aulas de Educação Física, tendo por conteúdo o esporte e, em específico, os jogos esportivos coletivos (JECs). Foi desenvolvida uma revisão bibliográfica dos termos citados e, a partir desta, o estudo avança para a proposição de um livro didático em educação física na temática dos JECs, considerando dois referenciais: um técnico-tático e outro sócio-educativo. Para tal, recorremos a métodos provenientes da área da lingüística, com o desenvolvimento de uma Seqüência Didática que permitiu a seleção e distribuição dos conteúdos a serem apresentados no LD de forma ordenada e criteriosa. O foco nos JECs se justifica pela sua inserção sócio-cultural e pela necessidade de transformar estudos mais recentes em novos procedimentos pedagógicos para a prática dessas modalidades. O livro didático, bem como a preparação adequada dos profissionais que o utilizarão, é apontado como facilitador no processo de ensino, vivência e aprendizagem dos jogos esportivos coletivos.
Sport Pedagogy: text books applied to team sports
Keywords: Sport Pedagogy; Physical Education; Team sports; Textbook